’Millennials’ as potential change agents for a different construction future: exploring visions and ambitions. - ASLANZADEH, DONIA (My University, 2017)
Generation studies of workforces ‘at work’ are trying to establish the connection between work practices and age-group variables. Generation characteristics are often considered as being socially constructed, meaning that age cohorts share certain socio-historical mediated experiences. ‘Millennials’ is the generation born in the 1980s and 1990s, and is one of the most studied generations. The individuals were born in an era of internet and high-speed communication, and are therefore accustomed to rapid technology changes and a socially networked world. Besides being open towards technology, they are also characterized as often changing jobs and being reluctant to ‘do time’ in order to get promoted. The purpose of this thesis is to explore millennials as potential change agents for a different construction future. The perceptions of 13 university students who are either just about to start or have just started their careers in the construction industry (i.e. 0-3 years) have been examined through an interview study. The interviews focus on: 1) their impressions of work life in construction so far and 2) their expectations and visions regarding their future in construction. The findings include different views on how the industry is perceived, the experiences of others’ expectations as well as stories from the construction sites. Furthermore, the dream projects of the interviewees are presented but also the projects that they reject. Lastly, some of their demands to stay at a company and how they make changes are presented. Drawing on the institutional theory, particularly institutional work and institutional entrepreneurs the individuals potential to create a different construction future is examined.
Keywords: Samhällsbyggnadsteknik; Civil Engineering